Orexin dual receptor antagonists, zolpidem, zopiclone, eszopiclone, and cognitive research: A comprehensive dose-response meta-analysis - Zhou, Mengzhen; Tang, Jiyou; Li, Shasha; Li, Yaran; Zhao, Mengke (Frontiers in Human Neuroscience, 2023)
Background About one-third of adults have trouble sleeping, ranging from occasional difficulty to chronic insomnia, along with difficulty maintaining sleep. Many studies reported that the long-term use of hypnotics can cause brain dysfunction and damage cognition. Objective The objective of the study is to evaluate whether low, medium, and high doses of orexin dual receptor antagonists (DORA), zopiclone (ZOP), eszopiclone (ESZ), and zolpidem (ZST) can impair cognition. Methods From the beginning through September 20, 2022, PubMed, Embase, Scopus, the Cochrane Library, and Google Scholar were searched. Randomized controlled trials (RCTs) assessing the therapeutic effects of DORA, eszopiclone, and zopiclone for sleep and cognitive function were included. The primary outcomes were indices related to the cognitive profile, including memory, alertness, execution and control function, and attention and orientation. The secondary outcomes were indices related to sleep and adverse events. The standard mean difference (SMD) was generated for continuous variables. Certain data were captured from figures by GetData 2.26 and analyzed using RStudio 4.2. Results Finally, a total of 8,702 subjects were included in 29 studies. Compared with the placebo, the DSST (Digit Symbol Substitution Test) scores of low, medium, and high doses of DORA were SMD = 0.77; 95% CI: 0.33–1.20; SMD = 1.58; 95% CI: 1.11–2.05; and SMD = 0.85; 95% CI: 0.33–1.36, respectively. The DSST scores of zolpidem at low, medium, and high doses were SMD = −0.39; 95% CI: 0.85–0.07; SMD = −0.88, 95% CI: −2.34–0.58; and SMD = −0.12, 95% CI: −0.85–0.60, respectively. Zopiclone's DSST scale score was SMD = −0.18; 95% CI: −0.54–0.18. In addition, the total sleep time (TST) of low, medium, and high doses of DORA was SMD = 0.28, 95% CI: −0.15–0.70; SMD = 1.36, 95% CI: 0.87–1.86; and SMD = 2.59, 95% CI: 1.89–3.30, respectively. The TST of zolpidem with low, medium, and high doses was SMD = 1.01, 95% CI: 0.18–1.83; SMD = 1.94, 95% CI: 0.46–3.43; and SMD = 1.71, 95% CI: 0.86–2.56, respectively. The TST of low, medium, and high doses of eszopiclone was relatively SMD = 2.03, 95% CI: −0.21–4.27; SMD = 2.38, 95% CI: 1.35–3.42; and SMD = 1.71, 95% CI: 0.60–2.82. Zopiclone's TST was SMD = 2.47, 95% CI: 1.36–3.58. Conclusion We recommend DORA as the best intervention for insomnia because it is highly effective in inducing and maintaining sleep without impairing cognition. Although zolpidem has a more pronounced effect on maintaining sleep, it is best to reduce its use because of its side effects. Eszopiclone and zopiclone improved sleep quality, but their safety in cognition remains to be verified.